Aksesibilitas Informasi dan Pengetahuan Masyarakat Towani Tolotang Terhadap Produk, Fitur Produk dan Preferensi Perbankan Syariah di Kota Parepare - Saleh, Muhammad; Syarifuddin, Mustika (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2023)
This study explores the accessibility of information and knowledge among the Towani Tolotang community regarding products, product features, and preferences in Shariah banking in the city of Parepare. The research aims to address two main questions: 1) Is there a correlation between the accessibility of information and the Towani Tolotang community's preferences towards products, product features, and Shariah banking in the city of Parepare? 2) Does the combined effect of the accessibility of information and knowledge among the Towani Tolotang community have an impact on product preferences and product features in Shariah banking in the city of Parepare? The study employs a quantitative field research methodology and a positivist approach. The sample size consists of 88 individuals selected from a population of 771 Towani Tolotang community members using Isaac and Michael's random sampling formula. The data collection methods include questionnaires, observation, and documentation. Multiple linear regression analysis is used to process and analyze the data. The research findings indicate that there is a significant correlation between the accessibility of information and the Towani Tolotang community's preferences towards products, product features, and Shariah banking in the city of Parepare. The study further reveals that the combined effect of the accessibility of information and knowledge among the Towani Tolotang community has a significant impact on product preferences and product features in Shariah banking in the city of Parepare.